2006
DOI: 10.1016/j.jcta.2005.07.004
|View full text |Cite
|
Sign up to set email alerts
|

On Rado's Boundedness Conjecture

Abstract: We prove that Rado's Boundedness Conjecture from Richard Rado's 1933 famous dissertation Studien zur Kombinatorik is true if it is true for homogeneous equations. We then prove the first nontrivial case of Rado's Boundedness Conjecture: if a 1 , a 2 , and a 3 are integers, and if for every 24-coloring of the positive integers (or even the nonzero rational numbers) there is a monochromatic solution to the equation a 1 x 1 + a 2 x 2 + a 3 x 3 = 0, then for every finite coloring of the positive integers there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The following straightforward lemma [FK05] is useful in proving that certain colorings are free of monochromatic solutions to particular linear equations.…”
Section: Minimal Colorings Over the Rationalsmentioning
confidence: 99%
“…The following straightforward lemma [FK05] is useful in proving that certain colorings are free of monochromatic solutions to particular linear equations.…”
Section: Minimal Colorings Over the Rationalsmentioning
confidence: 99%
“…In fact, Fox and Radoicic show that dor(a, b) ≤ 6 for all (a, b) = (1, 1). Their proof makes use of a result, due to Fox and Kleitman [13], which states that if a linear homogeneous equation in three variables is 24-regular, then it is regular. In [15], it is shown that 2 ≤ dor(a, 2a − 2) ≤ 4 for all a ≥ 2; that dor(a, 2a + j) ≤ 4 for 1 ≤ j ≤ 5; and that dor(a, 2a + 1) ≤ 3 for all a ≥ 1.…”
Section: Generalizations Of Arithmetic Progressionsmentioning
confidence: 99%
“…For b ≥ 0, let g(b) be the least positive integer (if it exists) such that for every 2-coloring of [1, g(b)] there is a monochromatic set of the form x, x + d, x + 2d + b. They showed that for b even, 2b + 10 ≤ g(b) ≤ 13 2 b + 1. The upper bound was improved by the present paper's second author, to 9 4 b + 9, who also conjectured that for b ≥ 10 even, g(b) = 2b + 10 [20].…”
Section: Generalizations Of Arithmetic Progressionsmentioning
confidence: 99%
“…The case when b = 0, which is also referred to as "L is homogeneous", was actively studied due to its close ties to other subjects such as Sidon sets, progression-free sets, and Rado's boundedness conjecture. See [12][13][14] for recent results on L-free sets where L is a homogeneous linear equation, and see [9,17] for details regarding Rado's boundedness conjecture. Also, the complexity of finding a maximum L-free set is known to be NP-complete in almost all cases, see [7,16] for recent results.…”
Section: Introductionmentioning
confidence: 99%